2018
DOI: 10.1038/s41598-018-33453-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel AICARFT inhibitor which potently elevates ZMP and has anti-tumor activity in murine models

Abstract: AICARFT is a folate dependent catalytic site within the ATIC gene, part of the purine biosynthetic pathway, a pathway frequently upregulated in cancers. LSN3213128 is a potent (16 nM) anti-folate inhibitor of AICARFT and selective relative to TS, SHMT1, MTHFD1, MTHFD2 and MTHFD2L. Increases in ZMP, accompanied by activation of AMPK and cell growth inhibition, were observed with treatment of LY3213128. These effects on ZMP and proliferation were dependent on folate levels. In human breast MDA-MB-231met2 and lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It is a folate competitive non-classical anti-folate inhibitor selective for AICAR TFase relative to other folate dependent enzymes [66]. In vivo studies have shown that LSN3213128 is orally bioavailable and that it demonstrates anti-tumor activity in murine models [66,67]. To data there are no records of any specific ATIC inhibitors in active clinical development.…”
Section: Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a folate competitive non-classical anti-folate inhibitor selective for AICAR TFase relative to other folate dependent enzymes [66]. In vivo studies have shown that LSN3213128 is orally bioavailable and that it demonstrates anti-tumor activity in murine models [66,67]. To data there are no records of any specific ATIC inhibitors in active clinical development.…”
Section: Inhibitorsmentioning
confidence: 99%
“…The current status of the development of inhibitors targeting the four enzymes described in this review is summarized in Table 1. 3PO [46] yes [46] yes [46] no PFK15 [48] yes [48] yes [48] no PFK158 [48] yes [49] yes [49] NCT02044861 [50] PFK-2 activity of PFKFB4 5MPN [51] yes [51] yes [51] no ATIC AICAR TFase BW1540 [57] no no no AICAR TFase BW2315 [57] no no no AICAR TFase LSN3213128 [66] yes [66,67] yes [66,67] no LTA 4 H epoxide hydrolase and aminopeptidase activities Acebilustat no available data no available data no (1) epoxide hydrolase and aminopeptidase LYS006 [105] yes [105] yes [105] no (1) epoxide hydrolase RH00633 [112] yes [112] no no…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…Thus, the use of certain antifolates as inhibitors of these two enzymes have been demonstrated to be another way to disrupt the normal DNA synthesis in highly multiplying cells. Some non-classical antifolates have been synthesized and successfully inhibit tumor growth both in vitro and in vivo [25,26]. However, this approach cannot be applied for P. falciparum infections because it lacks of the necessary enzymes for the de novo purine synthesis [27].…”
Section: Mechanisms Of Action Of Antifolatesmentioning
confidence: 99%
“…LSN3213128 is a potent antifolate inhibitor of AICARFT. Treatment with this inhibitor in a mouse-based triple-negative breast cancer xenograft model showed inhibition of tumor growth ( 17 ). Considering that the experiments were performed using triple-negative breast cancer, but based on the correlations we observed between the expression of ATIC and the survival outcome of HER2-positive breast cancer, the targeted ATIC products may be more toxic to HER2-positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%